Productivity of the company: main types of measures and different evaluation approaches - Bendarkawi, Anass (Revue Internationale du Chercheur, 2020)
Measuring and planning are behaviors necessary for progress and knowledge, and we are right to say that "we only know what we measure». Indeed, measure in order to control, it is also transforming vague perceptions into concrete indicators. Measure productivity, it is to contribute to efficiency and effectiveness. So, evaluation is necessary for the one who projects improve productivity in your business or at national level. However, the success of its measurement is conditioned by the participation of all employees (company managers, workers, employers, unions, public institutions). Many company managers hesitate to measure the productivity of their business because the concept of productivity remains elusive and they don’t know how to measure it. This article provides an opportunity to examine the concept of productivity and discusses critical questions of measurement and evaluation at the enterprise level.